Research on optimization of approach procedures for airports in an alpine environment - Lu, Li; Lai, Xin; Jiang, Junliang; Zhou, Juncheng (Frontiers in Environmental Science, 2024)
Obstacles in alpine environments pose significant challenges to aircraft safety during terminal operations. Key challenges include constraints from obstacles within the terminal clearance area and the labor-intensive manual calculations of flight procedures. The focal point of concern lies in the design of approach procedures, particularly due to the heightened risk of collisions with obstacles during the descent segment in such terrain. To address these challenges, initially, processing the terrain data, visualizing and extract the topographic data of the alpine airport by adopting bi-cubic bspline interpolation and cellular automatic machine model. Then, twice improving A* path algorithm to make sure it can obey with the standards of flight procedure design, utilizing the improved A* path algorithm to design approach procedures in this research. Due to the fuel consumption is directly connected with the economy of aviation companies, so finally, employing the fuel consumption evaluation model to select the most efficient approach flight procedures. This research takes a case study of a Yunnan airport, simulates and designs the optimized approach procedures by A* path algorithm and evaluation based on fuel consumption. Results indicate that the parameters of optimized approach procedures align with the regulation of flight procedure design and meet the requirements of real flight operation. Therefore, the core thinking of this research can provides a feasible idea for flight procedures with the alpine airports, and have the potential to reduce workload and enhance operational efficiency.